German political decisions on armament and arms exports examined under the concept of the military-industrial complex - Paul Saupe (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
The concept of the 'military-industrial complex'- which describes an alliance between a nation's military troops, its defense industry as its main supplier, and parts of the political apparatus - is already commonly used when speaking about the US situation. The paper investigates whether the use of this term can be justified in the context of Germany, focusing on the procurement practices of the German unified armed forces (Bundeswehr), the arms exporting practices of German corporations, and the lobbying power of the German defense industry.
Keywords: F51; F52; K23; 330; Military-Industrial Complex; German defense industry; armament exports